Separation of L-arginine and L-citrulline in red and yellow crimson watermelon (citrullus lanatus) juices extract using HPLC gradient mode - Ridwan, Rasdin; Abdul Razak, Hairil Rashmizal; Adenan, Mohd Ilham; Md Saad, Wan Mazlina (Faculty of Science and Technology, Universiti Kebangsaan Malaysia, 2018)
Watermelon (Citrullus lanatus) is a nutritious fruit that has attracted scientific interest due to its phytonutrient content including carotenoids and amino acids. Watermelon juice is the richest known source of amino acids including L-arginine and L-citrulline. For a complete separation of amino acids in watermelon juices, a gradient mode of reverse phase high performance liquid chromatography (RP-HPLC) with UV detection was utilised owing to its supremacy over isocratic mode. This present study was aimed at achieving good separation of chromatography profiles and baseline between L-arginine and L-citrulline in red and yellow crimson watermelon juice extract. The edible parts of watermelons were juiced, stored at – 80 oC and freeze dried to obtain dried juice powder. Samples were analysed by gradient mode of RP-HPLC using 0.1% orthophosphoric acid in water (v/v) and acetonitrile as mobile phase A and B. The chromatograph separation was performed using Gemini C18 column at a flow rate of 1.0 mL/min, maintained temperature at 25 oC while detection was made at four different wavelengths; 195 nm, 200 nm, 207 nm and 210 nm with total analysis time of 35 min. Excellent chromatographic separation was achieved at conditions of gradient elution (0%B - 95%B, 0-18 minutes and 95%B, 18-23 minutes, 95%B-0%B, 23-25 minutes, 0%B, 25-35 minutes) with baseline between L-arginine and L-citrulline in both watermelon juice extracts. The gradient mode used in this RP-HPLC successfully achieved efficient separation of chromatographic profile for amino acids, L-arginine and L-citrulline in the red and yellow crimson watermelon juice extracts.